Conflict, political ecology and dilemma of reclamation: Analysis of power relation on Bay reclamation in capital city - Mutia, Elok F. (Institute for Advanced Science Social, and Sustainable Future, 2024)
The issue of the Jakarta Bay reclamation originated from conflict between two groups, institutions who support and reject the project. This shows that there are problems regarding the policies issued. Through political ecology, this research aims to explain the power relation conflict in Jakarta Bay Reclamation. Descriptive qualitative design is used in this study to clarify the phenomena both structurally and deductively. Through in-depth interviews, the data and information analysis results were gathered, as well as studies and policy analysis. The research will deeply elaborate on influence of power relations that shape Government policies' intricate planning and management of Jakarta Bay Reclamation.